Hubungan Usia dengan Benign Prostate Hyperplasia dan Adenokarsinoma Prostat di Rumah Sakit Bethesda Yogyakarta - Jennifer Isabel Roberth; Jonathan Willy Siagian; Tejo Jayadi; Hariatmoko (Jurnal MedScientiae, 2022)
Age is a risk factor for the occurrence of Benign Prostate Hyperplasia (BPH) and prostate adenocarcinoma. The prevalence of BPH increases as the size of the prostate gland itself increases in older men. Prostate adenocarcinoma is the most common type of prostate cancer. In 2020, the incidence of prostate cancer is fifth in the male sex. Older men show an increased incidence of BPH and prostate adenocarcinoma compared to younger men. This study was conducted to determine the relationship between age with BPH and prostate adenocarcinoma in Bethesda Hospital Yogyakarta. The design of this study was cross-sectional using 62 medical records belonging to Bethesda Hospital Yogyakarta in 2015-2019 which were taken using the consecutive sampling method. Data were analyzed using Fisher Exact Test and obtained p value=0.048 (p<0.05). The results of this study indicate there is a relationship between age and BPH and prostate adenocarcinoma.